(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The research aims to use the Neutrosophic Logic, which adopts the logic of non-determinants, in treating the missing values in educational and psychology scales and tests, and to derive the necessary equations for the Cronbach’s Alpha consistency equation